Peran Tata Letak Ruang Perpustakaan terhadap Kenyamanan Pemustaka di Dinas Kearsipan dan Perpustakaan Provinsi Sumatera Barat - Cahyani, Amelia Dwi; Rahmah, Elva; Marlini, Marlini (Lembaga Yasin AlSys, 2026)
The layout of library spaces is a key factor influencing users’ comfort in utilising library services, yet studies that specifically explore the role of spatial layout in user comfort at regional public libraries from a user-experience perspective remain relatively limited. This study aimed to analyse the role of library space layout in supporting user comfort at the Dinas Kearsipan dan Perpustakaan Provinsi Sumatera Barat, with a particular focus on the arrangement of reading areas, shelving, ease of mobility, lighting, and overall room conditions. A qualitative method with a descriptive qualitative design was employed through in-depth interviews and direct observation of library users selected via purposive sampling based on their experience in using the library space. Data were analysed through the stages of data reduction, data display, and conclusion drawing using a thematic approach. The findings show that, overall, the library’s spatial layout has supported user comfort, particularly through the separation of reading areas and collection areas as well as the relatively orderly arrangement of facilities; the reading room is generally perceived as comfortable and conducive for reading and studying activities, while the placement of shelving assists users in locating materials. Nevertheless, several constraints were identified, including narrow aisle spacing between shelves in certain areas, mismatches between collection placement and classification numbers, and uneven lighting. The study concludes that the library’s spatial layout plays a crucial role in shaping user comfort but still requires ongoing optimisation. The implications highlight the need for more adaptive spatial planning, improved lighting quality, and more consistent collection management to enhance user comfort and the overall quality of public library services.